(untitled) (Journal of Economic Additions, 2025)
Enter This study aims at examining the effect of sukuk issuances in Malaysia on the domestic investment and the foreign direct investment during 2001-2024. Findings show a positive short-term effect for sukuk issuances in Malaysia on both domestic investment and foreign direct investment during the study period. However, a positive long-term effect was observed only on the foreign direct investment. In addition, the effect on the domestic investment was found to be greater than on the foreign direct investment. Jel Classification Codes: G23, E22,F21